Global Health Education Amidst COVID-19: Disruptions and Opportunities - Stevan Weine; Maarten Bosland; Chandrika Rao; Marcia Edison; Daniel Ansong; Stacey Chamberlain; Agnes Binagwaho (Ubiquity Press, 2021)
This viewpoint examines the impact of COVID-19 travel bans and remote education on the global health education of students from high-income countries (HIC) and low- and middle-income countries (LMIC) and explores potential opportunities for strengthening global health education based upon more dispersed and equitable practices. Global health is unique in the opportunities it can offer to students during the pandemic if programs can manage and learn from the pandemic's many challenges. Global health educators can: shift to sustainable remote engagement and mobilize resources globally to facilitate this; collaborate with partners to support the efforts to deal with the current pandemic and to prepare for its next phases; partner in new ways with health care professional students and faculty from other countries; collaborate in research with partners in studies of pandemic related health disparities in any country; and document and examine the impact of the pandemic on health care workers and students in different global contexts. These strategies can help work around pandemic travel restrictions, overcome the limitations of existing inequitable models of engagement, and better position global health education and face future challenges while providing the needed support to LMIC partners to participate more equally.